IMPLEMENTASI PENDIDIKAN LITERASI FINANSIAL ANAK USIA DINI: STUDI KASUS DI PAUD BANJARMASIN - Mahyuddin Noor; Yuliana Nurhayati; Maulidha (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2023)
Introduction to financial literacy knowledge from an early age will make children accustomed to managing finances properly in the future. This study aims to analyze the learning process activities in developing early childhood financial literacy education in Early Childhood integrated Islamic Baitul Makmur Banjarmasin. This study uses a qualitative approach with a case study method. The results showed that the implementation of early childhood financial literacy in early childhood integrated Islamic Baitul Makmur Banjarmasin still needs to be improved; existing activities so far only in the form of saving and Friday blessing activities; there are no more specific activities related to the development of early childhood financial literacy. Saving activities are carried out as a daily routine. At the same time, the Friday blessing is a sharing activity or alms, which will be the result of the money alms will be donated when Ramadan arrives. Researchers provide advice in improving financial literacy, from the use of media such as money kid, media to get to know money, its types, and amounts, as well as other activities in the form of playing buying and selling and field practices.